1989
DOI: 10.3109/02699058909029638
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and other predictors of cognitive recovery after severe head injury

Abstract: The research examined the effects of alcohol and other variables on cognitive outcome after severe head injury. Alcohol consumption habitually and at the time of injury were strongly related, and both were related to age and educational level but not injury severity. Covariance analysis to remove the effects of age and education showed a reduction in the main effects, so that only alcohol consumption at injury was a significant predictor of memory, but not other cognitive areas late after injury. There were si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
29
2
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 14 publications
4
29
2
1
Order By: Relevance
“…Similar findings are also evident in other cognitive and behavioral measures wherein alcohol users manifest lower cognitive status at hospital discharge following a TBI as measured by the Rancho Level of Cognitive Functioning (Sparadeo and Gill, 1989), and post-injury measures of verbal learning and memory (Brooks et al, 1989;Ronty et al, 1993;Tate et al, 1999), general intellect and verbal reasoning (Dikmen et al, 1993;Kaplan and Corrigan, 1992;Kelly et al, 1997b), visual-spatial functioning (Tate et al, 1999), and rehabilitation outcome (Corrigan et al, 1997).…”
Section: Introductionsupporting
confidence: 60%
“…Similar findings are also evident in other cognitive and behavioral measures wherein alcohol users manifest lower cognitive status at hospital discharge following a TBI as measured by the Rancho Level of Cognitive Functioning (Sparadeo and Gill, 1989), and post-injury measures of verbal learning and memory (Brooks et al, 1989;Ronty et al, 1993;Tate et al, 1999), general intellect and verbal reasoning (Dikmen et al, 1993;Kaplan and Corrigan, 1992;Kelly et al, 1997b), visual-spatial functioning (Tate et al, 1999), and rehabilitation outcome (Corrigan et al, 1997).…”
Section: Introductionsupporting
confidence: 60%
“…In fact, as already described, some studies [13][14][15][16][17][18][19][20][21][22] have shown that acute intoxication and pre-injury alcohol abuse have a negative impact on PTA duration and outcomes, but other studies did not show a significant effect among the variables mentioned above [13,24,25] or showed only a modest relationship. Contradictory results were also found for length of stay (LOS) [16,21,23] where some studies did not shown a longer LOS for patients intoxicated upon admission or with a pre-injury history of alcohol abuse.…”
Section: Introductionmentioning
confidence: 94%
“…These measures are useful in the context of an acute hospital setting and meaningful to clinicians involved with patients post-TBI in this setting. Moreover, these outcome measures were chosen in order to be able to compare the results of the present study with previous work carried out in rehabilitation settings where these are frequently also used as well as measures of independence in self-care activities [15,17,25].…”
Section: Introductionmentioning
confidence: 99%
“…Their investigation revealed that positive blood alcohol levels at admission were associated with higher levels of agitation, lower cognitive status at time of hospital discharge, and longer stays in acute care settings. In addition, Brooks et al (1989) found that high blood alcohol levels at admission were related to worse performance on postinjury measures of verbal learning and memory. A later study provided evidence that patients with a history of excessive alcohol use have more severe brain abnormalities and a higher mortality rate (Ruff et al, 1990).…”
mentioning
confidence: 99%